Psychotropic Polypharmacy in Adults 55 Years or Older: A Risk for Impaired Global Cognition, Executive Function, and Mobility - Loggia, Gilles; Attoh-Mensah, Elpidio; Pothier, Kristell; Morello, Rémy; Lescure, Pascale; Bocca, Marie-Laure; Marcelli, Christian; Chavoix, Chantal (Frontiers in Pharmacology, 2020)
Objectives: With their broad spectrum of action, psychotropic drugs are among the most common medications prescribed to the elderly. Consequently, the number of older adults taking multiple psychotropic drugs has more than doubled over the last decade. To improve knowledge about the deleterious effects of psychotropic polypharmacy, we investigated whether there is a threshold number of psychotropic molecules that could lead to impairment of global cognition, executive function, or mobility. Furthermore, relationships between the number of psychotropic molecules and cognitive and mobility impairment were examined. Design: Cross-sectional study Setting: University Hospital of Caen (France) and advertisements in medical offices Participants: Community-dwelling older adults aged 55 and older (n = 177; 69.8 ± 9.3 years; 81% women) Measurements: Number of psychotropic molecules taken daily, global cognition assessed with the Mini Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA), processing speed with the Trail Making Test (TMT) A, executive function with the TMT B and TMT B-A, and mobility with the Time Up and Go (TUG). The threshold numbers of psychotropic molecules were determined by ROC curves analysis. Based on these threshold values, multinomial logistic regression adjusting for covariates was then performed. Results: Logistic regressions showed that the threshold of two daily psychotropic molecules, identified by the ROC curves analysis, increases the risk of impaired executive function (p = .05 and .005 for the TMT B and TMT B-A, respectively), global cognition (p = .006 and .001 for the MMSE and MoCA, respectively), and mobility (p = .005 for the TUG), independent of confounding factors, including comorbidities. Furthermore, psychotropic polypharmacy would affect mobility through executive functions. Conclusion: Impairment of global cognition, executive function, and mobility when as few as two psychotropic molecules are consumed in relatively healthy young older adults should alert physicians when prescribing combinations of psychotropic medications.